Tablet Effervescent dari Daun Umbi Jalar Ungu untuk Pencegahan Penyakit Degeneratif - Zahra Safira Yunar; Nur Dwi Wahyu Wibowo; Nia Nurul Imana (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
The prevalence of non-communicable degenerative diseases in Indonesia continues to rise, particularly affecting adolescents and productive age populations due to unhealthy lifestyle patterns and free radical exposure. Purple sweet potato leaves (Ipomoea batatas L.), a locally abundant resource often regarded merely as agricultural by-product, contain significant bioactive compounds including polyphenols, flavonoids, anthocyanins, and terpenoids demonstrating potent antioxidant properties with IC50 values of 47.99 ppm. This study employs a qualitative descriptive literature review approach, analyzing 28 scientific publications spanning 2018-2025 sourced from Google Scholar and PubMed databases to examine the potential of purple sweet potato leaves as effervescent tablet raw material for degenerative disease prevention. Findings reveal that bioactive constituents effectively neutralize free radicals, prevent lipid peroxidation, and protect cellular structures from oxidative damage linked to diabetes, cancer, and cardiovascular disorders. The effervescent tablet formulation provides strategic advantages including enhanced solubility, accelerated absorption rates due to elimination of disintegration processes, pleasant carbonation sensation masking unpleasant active ingredient taste, and superior gastrointestinal tolerance. This innovation offers promising prospects for degenerative disease prevention through local food resource utilization, though experimental validation regarding optimal formulation, effective dosage determination, and clinical efficacy assessment remains necessary for practical implementation.